Amplification of large scale magnetic fields in a decaying MHD system - Park, Kiwan (Physical review, 2017)
Dynamo theory explains the amplification of magnetic fields in the conducting fluids (plasmas) driven by the continuous external energy. It is known that the nonhelical continuous kinetic or magnetic energy amplifies the small scale magnetic field; and the helical energy, the instability, or the shear with rotation effect amplifies the large scale magnetic field. However, recently it was reported that the decaying magnetic energy independent of helicity or instability could generate the large scale magnetic field. This phenomenon may look somewhat contradictory to the conventional dynamo theory. But it gives us some clues to the fundamental mechanism of energy transfer in the magnetized conducting fluids. It also implies that an ephemeral astrophysical event emitting the magnetic and kinetic energy can be a direct cause of the large scale magnetic field observed in space. As of now the exact physical mechanism is not yet understood in spite of several numerical results. The plasma motion coupled with a nearly conserved vector potential in the magnetohydrodynamic (MHD) system may transfer magnetic energy to the large scale. Also the intrinsic property of the scaling invariant MHD equation may decide the direction of energy transfer. In this paper we present the simulation results of inversely transferred helical and nonhelical energy in a decaying MHD system. We introduce a field structure model based on the MHD equation to show that the transfer of magnetic energy is essentially bidirectional depending on the plasma motion and initial energy distribution. And then we derive α coefficient algebraically in line with the field structure model to explain how the large scale magnetic field is induced by the helical energy in the system regardless of an external forcing source. And for the algebraic analysis of nonhelical magnetic energy, we use the eddy damped quasinormalized Markovian approximation to show the inverse transfer of magnetic energy.